Analisis Komparatif Ketahanan Beton Normal terhadap Perendaman Air Laut Pantai Watu Ulo dan Air Sungai Bedadung Kabupaten Jember - ulil amri; Ilanka Cahya Dewi; Hilfi Harisan Ahmad (Jurnal Rekayasa Infrastruktur HEXAGON, 2026)
This study was conducted to determine the effect of different curing media on the development of the compressive strength of ordinary concrete. The curing media used included tap water, seawater from Watu Ulo Beach, and water from the Bedadung River. Prior to the compressive strength tests, the fresh concrete was first tested using the slump method to determine the consistency of the mixture. Compressive strength tests were conducted at 14 days, 28 days, and 56 days. The slump test results showed an average value of 7.8 cm, indicating that the concrete mix had good workability and was suitable for on-site construction. The compressive strength test results showed that all test specimens exhibited an increase in strength as the concrete aged. At 14 days, concrete immersed in fresh water produced the highest compressive strength. However, at 28 and 56 days, concrete immersed in seawater exhibited higher compressive strength values compared to the other immersion media. The compressive strength values at 28 days ranged from 20.97 to 24.82 MPa, meaning the resulting concrete can be classified as medium-strength structural concrete. These findings indicate that the type of immersion medium influences the development of concrete compressive strength during the curing period